The storyteller - Picoult, Jodi, 1966- (London : Hodder & Stoughton, 2013)
Sage Singer must decide what to do after she begins a friendship with Joseph Weber and he makes a confession about his past to her.
Adult.
Adult
Keywords: Bakers -- Fiction; Ex-Nazis -- Fiction; Friendship -- Fiction; Good and evil -- Fiction; Bakers -- Fiction; Friendship -- Fiction; Good and evil -- Fiction; National socialism -- Fiction